Analisis Pembangunan Teknologi Informasi dan Komunikasi di Indonesia Tahun 2015-2020 - Mefi Atalya Selan; Krismanti Tri Wahyuni (Politeknik Statistika STIS, 2022)
Information and communication technology in Indonesia continues to experience developments marked by the increase in ICT development index as a measuring tool for ICT development. However, the increase between regions in Indonesia is uneven, resulting in a digital divide which indirectly impacts on social and economic inequality between regions. This study aims to determine the condition of ICT and the factors that influence the development of ICT in Indonesia in 2015-2020. The analytical method used is descriptive analysis and inferential analysis with panel data regression. The results showed that per capita GRDP, household consumption expenditure for telecommunications, and the price index of the transportation, communication and financial services sub-group commodities have a significant and influential effect on the development of ICT in Indonesia. Meanwhile, government spending on ICT and the Covid-19 pandemic did not significantly affect the development of ICT in Indonesia.